Environmental DEA method for assessing productivity of European countries - Chodakowska, Ewa; Nazarko, Joanicjusz (Technological and Economic Development of Economy, 2017)
The article presents the concept of environmental efficiency analysis based on the method of Data Envelopment Analysis in the case of the existence of desirable and undesirable results. Theoretical considerations are illustrated by a case study of European countries and evaluation of productivity taking into account not only economic growth but also effects which are undesirable and impossible to eliminate entirely, such as the impact on the environment. The differences in the results are explained by the relationship between policies aiming at supporting research and development with the use of the Tobit regression model. The added value of this work is to propose an integration of environmental DEA method with the concept of technological competitors. The possibility of applying the concept of DEA to technological competition was presented in the form of classification and benchmarking of the European countries. It is concluded that European countries are highly diversified in regard to the efficiency of environmental performance.